Assessment for Inclusion in Higher Education: Promoting Equity and Social Justice in Assessment. - Dison, Laura (Critical Studies in Teaching and Learning, 2024)
Ajjawi, R., Tai, J., Boud, D. and Jorre de St Jorre, T. (Eds.). 2023. Assessment for Inclusion in Higher Education: Promoting Equity and Social Justice in Assessment. London: Routledge.